Brain Oscillations in Human Communication - Joachim Gross (Frontiers Research Topics, 2018)
Brain oscillations, or neural rhythms, reflect widespread functional connections between large-scale neural networks, as well as within cortical networks. As such they have been related to many aspects of human behaviour. An increasing number of studies have demonstrated the role of brain oscillations at distinct frequency bands in cognitive, sensory and motor tasks. Consequentially, those rhythms also affect diverse aspects of human communication. On the one hand, this comprises verbal communication; a field where the understanding of neural mechanisms has seen huge advances in recent years. Speech is inherently organised in a rhythmic manner. For example, time scales of phonemes and syllables, but also formal prosodic aspects such as intonation and stress, fall into distinct frequency bands. Likewise, neural rhythms in the brain play a role in speech segmentation and coding of continuous speech at multiple time scales, as well as in the production of speech. On the other hand, human communication involves widespread and diverse nonverbal aspects where the role of neural rhythms is far less understood. This can be the enhancement of speech processing through visual signals, thought to be guided via brain oscillations, or the conveying of emotion, which results in differential rhythmic modulations in the observer. Additionally, body movements and gestures often have a communicative purpose and are known to modulate sensorimotor rhythms in the observer. This Research Topic of Frontiers in Human Neuroscience highlights the diverse aspects of human communication that are shaped by rhythmic activity in the brain. Relevant contributions are presented from various fields including cognitive and social neuroscience, neuropsychiatry, and methodology. As such they provide important new insights into verbal and non-verbal communication, pathological changes, and methodological innovations.